Labour Education and Vocational Training in Germany: A Brief Historical Review - E. Yu. Esenina; L. N. Kurteeva; S. A. Osadcheva; A. I. Satdykov; H Kress (Russian State Vocational Pedagogical University, 2018)
Introduction. A historical overview is often quite useful in search for answers to some pressing issues. Learning from others can also help to cope with separate current problems. One of such problems encountered by modern Russian professional education is restoration and consolidation of its practice orientation through selection of an appropriate content and upbringing of youth in the course of pre-employment process. A considerable variety of material in this regard has been accumulated over the last several centuries in Germany.The aim of this paper was to analyse the cause-and-effect relationships of developmental priorities in the German professional pedagogy during the 18th - early 20th centuries.Methodology and research methods. System and comparative approaches were used as main methodological tools. The leading method was a comparative retrospective analysis, which allowed the authors to compare various scientific resources. In addition, the approaches of goal-setting and formalisation of expected results were applied. The content analysis and systematisation of documents and other historical and pedagogical resources were employed. In view of information extensiveness, the selection was compiled with the principle of necessity and sufficiency, i. e. reduction of excess data when maintaining the completeness of facts for continued use.Results and scientific novelty. The stages of formation and development of labour school were identified according to the ideas of the German scientists and the educational practice accepted in Germany during the considered historical period. The main directions of training through activity were characterised: philanthropinism, manualism, professionalism and activism. The influence of social and economic conditions on formation and transformation of various educational concepts was demonstrated, which constant despite everything was a combination of fundamental and applied components of vocational training. The continuity of pedagogical theory and practice of the past in the modern system of the German professional education was shown.Practical significance. The findings obtained by the Russian-German research team can be useful when developing and implementing flexible and adaptive differentiated curricula into modern vocational education in Russia.